2009
DOI: 10.1186/1742-2094-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory responses of peripheral blood mononuclear cells from multiple sclerosis patients upon in vitro incubation with the flavonoid luteolin: additive effects of IFN-β

Abstract: The study is aimed to determine the role of luteolin (3',4',5,7-tetrahydroxyflavone), alone and in combination with human interferon-beta (IFN-β), in modulating the immune response(s) of peripheral blood mononuclear cells (PBMCs) isolated from multiple sclerosis (MS) patients. PBMC proliferation in the presence or absence of these drugs was determined and the production of proinflammatory cytokines (IL-1β, TNF-α), and the ratio of cell migration mediator MMP-9, and its inhibitor, TIMP-1 was assessed in the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 60 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…Luteolin has also been found to have an antiviral effect and shows a synergistic effect with IFN-β in modulating the immune responses of peripheral blood mononuclear cells isolated from multiple sclerosis patients, thus, it is proposed as a promising adjuvant for multiple sclerosis therapy. 21,22) Although its mechanism in these effects was still unknown, our finding that luteolin potently activated the JAK/ STAT pathway sheds new light on its preclinical study. Luteolin is found to be a protein kinase C (PKC) inhibitor, whereas PKCβ is found to negatively regulate IFN-induced JAK/STAT activation.…”
Section: Discussionmentioning
confidence: 97%
“…Luteolin has also been found to have an antiviral effect and shows a synergistic effect with IFN-β in modulating the immune responses of peripheral blood mononuclear cells isolated from multiple sclerosis patients, thus, it is proposed as a promising adjuvant for multiple sclerosis therapy. 21,22) Although its mechanism in these effects was still unknown, our finding that luteolin potently activated the JAK/ STAT pathway sheds new light on its preclinical study. Luteolin is found to be a protein kinase C (PKC) inhibitor, whereas PKCβ is found to negatively regulate IFN-induced JAK/STAT activation.…”
Section: Discussionmentioning
confidence: 97%
“…We showed that luteolin can inhibit mast cell activation and mast cell-dependent superstimulation of activated T cells with or without stimulation by MBP [80]. Luteolin can also inhibit activation of peripheral lymphocytes from MS patients [311], and it was, therefore, proposed as adjuvant therapy for MS [312]. …”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Luteolin has synergistic effect with IFN-b in inhibiting activation of peripheral blood mononuclear cells from MS patients (Sternberg et al, 2008(Sternberg et al, , 2009. A novel luteolin analog, tetramethoxyluteolin, is more potent that luteolin (Weng et al, 2014b), making it an attractive molecule for drug development especially since it is also less metabolized (Walle, 2007).…”
Section: Il-33 In Autoimmune and Inflammatory Disordersmentioning
confidence: 99%